2020
DOI: 10.24191/jeeir.v8i3.8884
|View full text |Cite
|
Sign up to set email alerts
|

Do different Halal certificates have different impacts on Muslims?

Abstract: The Halal is one of the most essential concepts for Muslims and many associations worldwide issue Halal certificates of their own. We investigated in what ways Muslims treat different Halal certificates using instant coffee as an example. We can regard that if Muslims perceive different values for different Halal certificates, they regard Halal certificate more like a commercial certificate while if they perceive almost the same value, they regard the certificate as the religious certificate. We conducted a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Besides, scholars have recently found that the halal logo positively influences the willingness to pay towards halal-certified food among Muslim consumers in Malaysia (Hamzah et al, 2020;Hosseini et al, 2019). This finding is also supported by the research results of Kawata and Salman (2020), who found that consumers' willingness to pay increases for products having a halal logo compared to those that do not.…”
Section: Halal Logomentioning
confidence: 83%
See 1 more Smart Citation
“…Besides, scholars have recently found that the halal logo positively influences the willingness to pay towards halal-certified food among Muslim consumers in Malaysia (Hamzah et al, 2020;Hosseini et al, 2019). This finding is also supported by the research results of Kawata and Salman (2020), who found that consumers' willingness to pay increases for products having a halal logo compared to those that do not.…”
Section: Halal Logomentioning
confidence: 83%
“…In line with this, Nasution and Rossanty's (2018) research shows that the country of origin has a positive influence on the purchasing behaviour of Muslim consumers in buying imported food in Indonesia. Kawata and Salman (2020) also found that willingness to pay may differ for products from certain countries. For example, due to the popularity of Vietnamese coffee, Vietnamese customers were shown to be more willing to pay for instant coffee than their Asian counterparts.…”
Section: Country Of Originmentioning
confidence: 99%
“…Many studies apply discrete choice models such as CEs to estimate Muslims' WTP for various products (Putri et al, 2017;Ahmed et al, 2019;Kawata and Salman, 2020) including mineral water (Kawata et al, 2018). The CE comprised three choice sets (Figure 3), each containing four choices.…”
Section: Study Sitementioning
confidence: 99%